Pengaruh Electronic Word of Mouth terhadap Keputusan Pembelian Produk Kosmetik Bibir Barenbliss di Bandar Lampung - Annisa Rizki Indriani; Dorothy RH Pandjaitan (Jurnal Bisnis Kreatif dan Inovatif, 2025)
Advancements in information technology have influenced changes in consumer behavior, particularly in making purchasing decisions, especially with the emergence of the Electronic Word of Mouth (EWOM) phenomenon on social media and e-commerce platforms. EWOM refers to the electronic dissemination of information or reviews about products, which many consumers rely on before deciding to purchase a product. This study aims to analyze how three main aspects of EWOM—intensity, Valence of Opinion, and content quality—affect purchasing decisions for Barenbliss lip cosmetic products in Bandar Lampung. This study uses a quantitative-descriptive approach, with data collected through a questionnaire distributed to consumers who have used Barenbliss products and have seen digital reviews about the product. The sample selected consists of consumers with direct experience with the product and who can provide insights into the influence of digital reviews on purchasing decisions. The data collected was analyzed using SPSS 25.0. The results show that all three independent variables—intensity, Valence of Opinion, and content quality—have a significant positive impact on purchasing decisions, either individually or collectively. All hypothesis tests showed significance values below 0.05, indicating that the hypotheses are accepted. These findings suggest that the more frequently consumers are exposed to product reviews, the higher the likelihood they will make a purchase. Positive reviews (Valence of Opinion) were found to enhance consumer trust in the product, while informative and high-quality content further strengthened the intention to purchase. Overall, this study emphasizes that EWOM plays a significant role in shaping consumer purchasing decisions. The intensity of reviews, positive Valence of Opinion, and content quality work together to increase the likelihood of purchasing Barenbliss products in Bandar Lampung.